Flower-petal-like Nb2C MXene combined with MoS2 as bifunctional catalysts towards enhanced lithium-sulfur batteries and hydrogen evolution. (1st February 2022) - Zong, Hui; Hu, Le; Gong, Shijing; Yu, Ke; Zhu, Ziqiang
Abstract: Efficient catalysts designed by reasonable heterostructure engineering have a bright prospect for lithium-sulfur batteries (LSBs) and hydrogen evolution reaction (HER). Here, we determined Nb2 C MXene and MoS2 to form heterojunction due to their high lattice adaptation. The unique flower-petal-like Nb2 C MXene was prepared by freeze-drying, the MoS2 growing on the surface of Nb2 C MXene by hydrothermal method. We applied the MoS2 /Nb2 C hybrids to LSB for the first time. The MoS2 /Nb2 C hybrids showed a specific capacity of 919.2 mAh g −1 at 0.2 C after 200 cycles with excellent retention of 92.2% when used as the cathode of LSBs. The MoS2 /Nb2 C electrode was used for HER under alkaline condition, which showed a Tafel slope of 65.1 mV dec −1, an overpotential of 117 mV at 10 mA cm −2 and excellent long-term robustness of HER performance. The mechanism of excellent properties of LSBs and HER activity were explained from the perspective of adsorption energy calculated according to the first principles. The adsorption activity of the MoS2 /Nb2 C heterojunction is much higher than that of bare MoS2 from the point of view of lithium polysulfides (LiPS) and hydrogen atoms. The heterostructure engineering of the MoS2 /Nb2 C hybrids is of guiding significance for green energy and energy conversion. Highlights: The flower-petal-like Nb2 C MXene can be combined with MoS2, forming the MoS2 /Nb2 C heterostructure. The MoS2 /Nb2 C catalyst can be used as LSB's cathode with good long-term stability. The MoS2 /Nb2 C catalyst has low overpotential for HER in 1 M KOH. DFT calculation indicate that the heterojunction structure accelerates polysulfide conversion and hydrogen evolution. Graphic abstract: Flower-petal-like Nb2 C MXene combined with MoS2 can be used as bifunctional electrocatalysts towards enhanced lithium-sulfur batteries and hydrogen evolution reaction. Image, graphical abstract